Current-mode four-phase quadrature oscillator using a MCCCCTA and grounded capacitors - Khaw-Ngam, Khachen; Lamun, Panit; Kumngern, Montree; Phasukkit, Pattarapong; Dejhan, Kobchai (My University, 2012)
A new current-mode four-phase quadrature oscillator circuit using a single modified current controlled current conveyor transconductance amplifier (MCCCCTA) and two grounded capacitors is presented. The oscillator provides four current outputs with 90° phase difference from high output impedance terminals. The condition of oscillation and the frequency of oscillation can be electronically and orthogonally tuned by adjusting bias currents of MCCCCTA. Non-ideal analysis and sensitivity study of the circuit are carried out. The results of circuit simulations are fully in agreement with the theoretical. © 2012 IEEE.
Keywords: current-mode; MCCCCTA; quadrature oscillator